A systematic molecular dynamics simulation study of temperature dependent bilayer structural properties - Zhuang, Xiaohong; Makover, Judah R.; Im, Wonpil; Klauda, Jeffery B. (Biochimica et biophysica acta, 2014)
Although lipid force fields (FFs) used in molecular dynamics (MD) simulations have proved to be accurate, there has not been a systematic study on their accuracy over a range of temperatures. Motivated by the X-ray and neutron scattering measurements of common phosphatidylcholine (PC) bilayers (Kučerka et al. BBA. 1808: 2761, 2011), the CHARMM36 (C36) FF accuracy is tested in this work with MD simulations of six common PC lipid bilayers over a wide range of temperatures. The calculated scattering form factors and deuterium order parameters from the C36 MD simulations agree well with the X-ray, neutron, and NMR experimental data. There is excellent agreement between MD simulations and experimental estimates for the surface area per lipid, bilayer thickness (DB), hydrophobic thickness (DC), and lipid volume (VL). The only minor discrepancy between simulation and experiment is a measure of (DB−DHH)/2 where DHH is the distance between the maxima in the electron density profile along the bilayer normal. Additional MD simulations with pure water and heptane over a range of temperatures provide explanations of possible reasons causing the minor deviation. Overall, the C36 FF is accurate for use with liquid crystalline PC bilayers of varying chain types and over biologically relevant temperatures. [Display omitted] •MD simulations of CHARMM36 PC lipids for the Lα phase ranging from 20 to 60°C•Excellent agreement with experimental X-ray and neutron scattering form factors•MD/CHARMM36 agrees with deuterium NMR order parameters at varying temperatures.•Slight inaccuracies are attributed to force field inaccuracies of water and alkane densities.